Description of two new species of jumping spider Colonus F.O. Pickard-Cambridge, 1901 (Araneae: Salticidae) from Brazil and Argentina - Rubio, Gonzalo Daniel (2023)
We present a taxonomic study with descriptions and illustrations of two new species of Colonus F.O. Pickard-Cambridge, 1901 (Araneae, Salticidae): Colonus gracilis sp. n. (♂♀) from Argentina, and Colonus alineae sp. n. (♂♀) from Argentina and Brazil. In addition, we present the first description of the female of C. melanogaster (Mello-Leitão, 1917).